QUADRUPLE TROUBLE: NUTRITIONAL MANAGEMENT OF A MULTIPLE GESTATION PREGNANCY IN A FILIPINO PRIMIGRAVID - Uy, Angelique Bea; Anonuevo-Cruz, Cecille (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Nutritional requirements among pregnant women vary according to pre-pregnancy bodyweight, BMI, trimester, and number of fetuses. Those bearing multiples require additional calories to promote adequate growth and development, and prevent pregnancy complications. We report the nutritional management of a 29-year-old Filipino primigravid bearing quadruplets on her 24th week age of gestation, admitted for preterm labor. CASE The patient was referred to Endocrinology service for sugar control while on dexamethasone therapy for fetal lung maturation, and nutritional upbuilding. She had histories of twin pregnancies from both her and her husband’s sides of family. No family history of diabetes, PCOS, and glycosuria noted, nor was she overweight or obese on her pre-pregnant state. Only dexamethasone was noted as a medication the patient had that could affect carbohydrate metabolism. CONCLUSION The nutritional recipe prescribed was 3500 kcal daily with 40% carbohydrates, 40% protein, and 20% fat, achieving adequate interval growths for the foetuses. Multivitamin supplements were also given daily. Infants were delivered live at 31 weeks AOG, with birth weights 1100 g, 640 g, 720 g, and 835 g, respectively, all small for gestational age.